Value Management Information System at SMK N 2 Padang Panjang - Fadilla, Nurhayatul (Jurnal Manajemen Informatika Medicom (JMI), 2024)
Values ​​are one of the important components in teaching and learning activities in schools which will later become inputs which are expected to become outputs that can balance and even develop the value of each student. Problems that occur in processing values ​​at SMKN 2 Padang Panjang are currently still written in manuals, and the delivery of values ​​is still using paper media, so a lot of time and effort is needed to process these values. I obtained this research from the method of observation, interviews and libraries, which surveyed directly to the field, interviewed directly with the school and looked for books in the library, and SDLC. The purpose of this research is to build a value information system that makes it easier to check and record, computerized student grade data reports. In addition, by being web-based, data information can be accessed at any time. This research has produced a value processing system that helps the work of teachers and homeroom teachers, this Information System which uses supporting technology in the form of PHP and MySQL database makes it easy for admins in this case homeroom teachers to access through any device during. This is done to build a system that helps in the processing and presentation of student value data information. This information system, which uses supporting technology in the form of PHP and MySQL database, makes it easy for admins, in this case homeroom teachers/teachers, to access them through any device. This is done to build a system that helps in the processing and presentation of student value data information. This information system, which uses supporting technology in the form of PHP and MySQL database, makes it easy for admins, in this case homeroom teachers/teachers, to access them through any device. This is done to build a system that